(untitled) (Acta Scientiarum. Biological Sciences, 2013)
Testate amoebae have a great potential for use in scientific researches due to their ecological characteristics such as abundance, wealth, and generation time. In this way, this study aimed to present a scientometric analysis to describe the evolution of the different advances in researches on testate amoebae and identify a temporal pattern in this evolution. The literature review was based on papers indexed by Thomson Reuters (www.isiwebofknowledge.com) and SciVerse Scopus (www.scopus.com). In total 562 papers were examined. Results showed a pattern of evolution in scientific studies, most with ecological approach with descriptive and predictive designs. At the global level, researches on testate amoebae progressed in both the number of articles published as well as in the areas studied, especially in Europe and North America. The low number of experimental studies and review articles can characterize the lack of more knowledge to be acquired, both from particular observations (descriptive studies) as well as the observations noted sufficiently predictive of work. In Brazil, studies with testate amoebae are still developing, concentrated in only some regions, but the increased number of studies in recent years allows the prediction of the same overall patterns of advance for Brazilian researches. Thus, we conclude that these organisms are being increasingly used as a tool response in ecological studies.